2012
DOI: 10.1016/j.molcel.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Proteins in the Nucleolus by Ribosomal Intergenic Spacer Noncoding RNA

Abstract: Cellular pathways are established and maintained by stochastic interactions of highly mobile molecules. The nucleolus plays a central role in the regulation of these molecular networks by capturing and immobilizing proteins. Here, we report a function for noncoding RNA (ncRNA) in the regulation of protein dynamics of key cellular factors, including VHL, Hsp70 and MDM2/PML. Stimuli-specific loci of the nucleolar intergenic spacer produce ncRNA capable of capturing and immobilizing proteins that encode a discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
306
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(312 citation statements)
references
References 53 publications
6
306
0
Order By: Relevance
“…In this study, the deletion of arginine motifs in the NoDS of Hsp70 prevents nucleolar accumulation as well as the precipitation of a peptide NoDS failed without arginines in the motif. 60 Sequence alignment of the NoLS for the human La protein with several other nucleolar localization domains of human proteins revealed a (R/K) (R/K) £ (R/K) motif appearing frequently as single or multiple copies and similar motifs had been known before. 61,62 The importance of arginines has also been shown for a number of RNA binding proteins with arginine rich motifs.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, the deletion of arginine motifs in the NoDS of Hsp70 prevents nucleolar accumulation as well as the precipitation of a peptide NoDS failed without arginines in the motif. 60 Sequence alignment of the NoLS for the human La protein with several other nucleolar localization domains of human proteins revealed a (R/K) (R/K) £ (R/K) motif appearing frequently as single or multiple copies and similar motifs had been known before. 61,62 The importance of arginines has also been shown for a number of RNA binding proteins with arginine rich motifs.…”
Section: Discussionmentioning
confidence: 74%
“…Key stress-related proteins like Hsc70/Hsp70 immediately translocate to the nucleolus during heat stress or acidosis (Audas et al, 2012;Banski et al, 2010;Welch and Feramisco, 1984).…”
Section: V454 Role Of the Nucleolus In Stress Responsementioning
confidence: 99%
“…Four stimuli-specific loci producing their own RNAs are currently denoted in the rIGS. They were termed IGS27RNA, IGS22RNA, IGS16RNA, and IGS pRNA [26][27][28]. Functional studies of these molecules have revealed new mechanisms for the regulation of rRNA expression, as well as a novel posttranslation regulatory pathway termed the nucleolar detention pathway.…”
Section: Long-term Regulationmentioning
confidence: 99%
“…Functional studies of these molecules have revealed new mechanisms for the regulation of rRNA expression, as well as a novel posttranslation regulatory pathway termed the nucleolar detention pathway. All proteins captured by rIGSlncRNAs contain the nucleolar detention signal (NoDS),i.e., a position-independent consensus sequence, which consists of at least one arginine motif (RRI/L) and a minimum of two hydrophobic triplets (LhL/v, where h represents a hydrophobic residue) [26]. These molecules have diverse functions in ubiquitination, proteasomal degradation, protein folding, and DNA replication and methylation, indicating that the NoDS may control important aspects of cellular life [27].…”
Section: Long-term Regulationmentioning
confidence: 99%
See 1 more Smart Citation